The Role of Animated Films Based on the Works of Alisher Navoi in Shaping Children's Worldview (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the cartoons screened by Alisher Navoi and their role in the upbringing of children, the analysis of the animated film "Sher ila Durroj".